• Or search :

# Idiom #31 Recursive factorial (simple)

Create the recursive function f which returns the factorial of the non-negative integer i, calculated from f(i-1)

```module x
implicit none
contains
recursive function f (i) result (res)
integer, intent(in) :: i
integer :: res
if (i <= 0) then
res = 1
else
res = f(i-1) * i
end if
end function f
end module x```
`function F (I : Natural) return Natural is (if I < 2 then 1 else I * F (I - 1));`
```unsigned int f(unsigned int i)
{
return i?i*f(i-1):1;
}```
```(defn f [i]
(loop [cnt i, acc 1N]
(if (zero? cnt) acc
(recur (dec cnt) (* cnt acc)))))
```
```unsigned int f( unsigned int i ) {
if ( i == 0 ) return 1;

return i * f( i - 1 );
}```
`int f(int i) => i == 0 ? 1 : i * f(i - 1)`
```int f(int i)
{
if (i == 0) return 1;
return i * f(i - 1);
}```
```uint f(in uint i) pure nothrow @nogc
in {
assert(i <= 12);
} body {
if (i == 0)
return 1;
else
return i * f(i - 1);
}```
`f(i) => (i == 0) ? 1 : i * f(i - 1);`
```defmodule Factorial do
def f(0), do: 1
def f(i) when i > 0 do
n * f(i-1)
end
end```
```f(0) -> 1;
f(I) -> I * f(I - 1).```
```func f(i int) int {
if i == 0 {
return 1
}
return i * f(i-1)
}```
```def f(i) { i == 0 ? 1 : i * f(i - 1) }
```
```f i = if i > 1 then f (i-1) * i else 1
```
```function f(i) {
return i<2 ? 1 : i * f(i-1);
}```
`const f = i => i === 0 ? 1 : i * f(i-1)`
```int f(int i) {
if (i == 0)
return 1;
else
return i * f(i - 1);
}```
```fun f(i: Int) = if (i == 0) 1 else i * f(i - 1)
```
```fun f(i: Int): Int = when (i) {
0 -> 1
else -> i * f(i - 1)
}
```
```(defun f (i)
(if (< i 2)
1
(* i (f (- i 1)))))```
```function f(n)
local function f_(factorial,n)
if n < 2 then return 1
return f_(factorial*n, n-1)
end
return f_(1,n)
end```
```unsigned f(unsigned i) {
return i?i*f(i-1):1;
}```
```function f(int \$i): int
{
if (\$i == 0) {
return 1;
}

return \$i * f(\$i - 1);
}```
```function f(\$i) {
if(\$i == 0) {
return 1;
}

return (\$i * f(\$i-1));
}```
```type
TPositiveInt = 0..MaxInt;

function _f(_i: TPositiveInt): Integer;
begin
if (_i < 2) then
Result := 1
else
Result := _f(_i - 1);
end; ```
```sub f {
my \$i = shift;
return \$i<2 ? 1 : \$i * f(\$i-1);
}```
```def f(i):
if i == 0:
return 1
else:
return i * f(i-1)```
`fac = Hash.new {|h, i| h[i] = i * h[i-1] }.tap {|h| h[0] = 1 }`
```f = Hash.new { |hash, i| hash[i] = i * hash[i -1] }
f[0] = 1
```
```fn factorial(num: u64) -> u64 {
match num {
0 | 1 => 1,
_ => factorial(num - 1) * num,
}
}```
```fn f(n: u32) -> u32 {
if n < 2 {
1
} else {
n * f(n - 1)
}
}```
```def f(i: Int): Int =
if (i > 1){
i * f(i-1)
} else{
1
}```
```(define (f i)
(if (> i 1)
(* (f (- i 1)) i)
1))```
`f := [:i | i = 0 ifTrue: [1] ifFalse: [i * (f value: i - 1)]].`
```Function f(i As Integer) As Integer
Return If(i = 0, 1, i * f(i - 1))
End Function```

programming-idioms.org